Tooth Mineralization: A Technical Note on the Moorrees-Fanning-Hunt Standards - Edward F. Harris; Andrea L. Buck (Dental Anthropology Association, 2002)
One of the largest, longitudinal studies of tooth mineralization is that described by Moorrees, Fanning and Hunt (J Dent Res, 1963) based on children growing up in Boston, Massachusetts, and Yellow Springs, Ohio. This short communication provides tables of the means and standard deviations, by sex, in order to make the data more accessible and usable than the graphic form of the information in the original article. Characteristics of the study and applications are discussed.